A collaborative model of community health nursing practice - Downie, Jill; Ogilvie, S.; Wichmann, Helen (eContent Management Pty Ltd, 2005)
This paper discusses a strategic collaborative partnership between a Western Australian university and a community health service based on a Practice-Research Model. The partnership has involved a senior academic (0.2 FTE) working in the community health setting as a Nurse Research Consultant since 1998. The first section of the paper draws on the nursing literature on collaborative models and describes the broad background to the partnership and development of the Model. The second section presents in detail the results of a recent evaluation that involved a brief survey and follow-up interviews to determine community health nurses' understanding and perceptions of the partnership Model. Three main themes emerged from the interviews: (1) Advancement of learning. This theme captured the extent to which the Nurse Research Consultant position helped to educate nurses and promote and develop research and best-practice; (2) Job satisfaction and self-confidence. This encompassed the extent to which participants felt nursing management were supportive of their professional education and pursuit of best-practice solutions, and (3) Situational opportunity. This theme reflected the more negative comments expressed by participants and related mostly to the restricted availability of Nurse Research Consultant and a focus on mainstream research priorities. The results suggest that the partnership Model provided the nurses with the opportunity to develop an increased understanding of the role of research in clinical practice and confidence in their own ability to reflect on current nursing practice. This allowed them to identify clinical problems in order to deliver and evaluate best-practice solutions, as evidenced by a change in attitude from the previous evaluation. However, it was also noted that the operational performance of the Model needs continual monitoring to ensure that all nurses have equitable access opportunities.